Creation of mythology of "historical guilt" of Russia during the psychological war of the XXI century - Kolomyts, Dmitriy Mikhailovich (International Journal of Psychosocial Rehabilitation, 2020)
The article it is about the role of myth-making in psychological warfare. Myth-making is understood as a kind of creativity in the field of creation of myths. When studying this issue, we should bear in mind that the myth-making of the XXI century is a historical, that is, an artificial ideological product created for political and social purposes. Discusses the mythology of Russophobia, created with the purpose of introduction in consciousness of the Russian population of historical nihilism. The methods of counteraction to the spread of destructive mythology are shown.